Brivaracetam in treating epileptic encephalopathy and refractory focal epilepsies in patients under 14 years of age. - Russo, Angelo; Cuteri, Vittoria; Bansal, Lalit; Bonanni, Paolo; Danieli , Alberto; Pini, Antonella; Gobbi , Giuseppe (Iranian Journal of Child Neurology, 2021)
Objectives: To analyze the efficacy and safety of Brivaracetam in pediatric patients with epileptic encephalopathy or unresponsive focal epilepsy. Materials & Methods: This retrospective study was performed on 8 pediatric patients with EE or unresponsive focal epilepsy. Inclusion criteria: (1) 14 years or younger, (2) history of refractory epilepsy, (3) at least 1 month of continuous therapy with BRV, and (4) at least 6 months of follow-up. Exclusion criteria: (1) variation of concomitant antiepileptic drugs during the previous and/or subsequent 4 weeks of the introduction of BRV, (2) levetiracetam in therapy, (3) an epilepsy secondary to a progressive cerebral disease, tumor, or any other progressive neurodegenerative diseases, and (4) a status epilepticus in the month before screening or during the baseline period. The efficacy of BRV was defined as ≥50% of seizure frequency reduction at the end of the follow-up compared to baseline. Results: All patients showed ≥50% seizure frequency reduction, of which 37.5% were seizure-free, 25% had a frequency reduction of ≥75% and 37.5% ≥ 50%. All patients with an epilepsy onset >12 months and duration of the epilepsy ≤6 years were seizure-free. The maximum effect was achieved at 2 mg/kg/day. Focal seizures showed a better response than epileptic encephalopathy. A remarkably positive effect of the Brivaracetam in patients with encephalopathy related to status epilepticus during sleep was noted. No relevant adverse events were noted. Conclusion: Brivaracetam was an effective and well-tolerated treatment in pediatric patients with epileptic encephalopathy or unresponsive focal epilepsy, especially when the epilepsy onset was >12 months and the epilepsy duration ≤6 years. The overall effect was not dose dependent. Brivaracetam could have an indication in encephalopathy related to status epilepticus during sleep.